Impact of the Three Gorges Dam on reproduction of four major Chinese carps species in the middle reaches of the Changjiang River - 黎明政 段中华 高欣 曹文宣 刘焕章 (Chinese journal of oceanology and limnology, 2016)
Silver carp （Hypophthalmichthys molitrix）, bighead carp （Aristichthys nobilis）, grass carp （Ctenopharyngodon idella）, and black carp （Mylopharyngodon piceus） are the four major Chinese carps and are commercially important aquaculture species in China. Reproduction of these carp has declined since the construction of the Three Gorges Dam （TGD） due to an altered water flow and thermal regime in the Changjiang （Yangtze） River. However, details of the changes in reproduction of the four species are not well understood. To assess the impact of the TGD on reproduction of the four carp, we investigated their eggs and larvae at Yidu City, which is 80 km below the TGD, during 2005-2012. We examined differences in larval abundance of the four species in the Jianli section （350 km downstream of the TGD） before （1997-2002） and after （2003-2012） construction of the TGD. Based on these observations, the first spawning date of the four species was delayed a mean of about 25 days after the dam was constructed. Mean egg abundance in the Yidu section of the river was 249 million and mean larval abundance was 464 million, which were significant decreases since the 1980s. Moreover, larval abundance in the Jianli section after the dam was constructed was significantly lower than that before construction （ANCOVA, P〈0.05）. The observed larval abundance accounted for only 24.66% of the predicted value in 2003 when the dam was first inundated. The present spawning grounds between the TGD and Yidu section of the river are very similar to those described in the 1980s, and some spawning grounds exist upstream of the TGD. Large free-flowing stretches upstream of the TGD and the creation of artificially flooded downstream reaches are needed to stimulate spawning and effectively conserve these four major Chinese carps species.